"y^{IV}-2y^{III}+2y^{II}=(3+2x)e^{-x}+e^{-x} \\sin x"
Solution find in form
"y=y_0+y_1+y_2"
1) "y_0" find from equation
"y^{IV}-2y^{III}+2y^{II}=0\\\\\n\\lambda ^4-2\\lambda^3+2\\lambda^2=0\\\\\n\\lambda_1=\\lambda_2=0, \\lambda_3=1-i, \\lambda_4=1+i\\\\\ny_0=C_1+C_2x+C_3e^x\\cos x+C_4e^x \\sin x"
2) "y_1" find in form
"y_1=(ax+b)e^{-x}"
for equation
"y^{IV}-2y^{III}+2y^{II}=(3+2x)e^{-x}\\\\\ny_1'=(a-ax-b)e^{-x}\\\\\ny_1''=(ax-2a+b)e^{-x}\\\\\ny_1'''=(3a-ax-b)e^{-x}\\\\\ny_1''''=(ax-4a+b)e^{-x}\\\\"
input in equation
"(ax-4a+b)e^{-x}-2(3a-ax-b)e^{-x}+\\\\\n+2(ax-2a+b)e^{-x}=(3+2x)e^{-x}\\\\\nx:a+2a+2a=2\\\\\nx^0:b-4a-6a+2b-4a+2b=3\\\\\na=\\frac{2}{5}\\\\\nb=\\frac{43}{25}\\\\\ny_1=(\\frac{2}{5}x+\\frac{43}{25})e^{-x}"
3) "y_2" find in form
"y_2=ke^{-x}\\cos x+me^{-x}\\sin x"
for equation
"y^{IV}-2y'''+2y''=e^{-x}\\sin x\\\\\ny'_2=(m-k)e^{-x}\\cos x-(k+m)e^{-x}\\sin x\\\\\ny''_2=-2me^{-x}\\cos x+2ke^{-x}\\sin x\\\\\ny'''_2=(2m+2k)e^{-x}\\cos x+(2m-2k)e^{-x}\\sin x\\\\\ny''''_2=-4ke^{-x}\\cos x-4me^{-x}\\sin x\\\\\n-4ke^{-x}\\cos x-4me^{-x}\\sin x-\\\\\n-2(2m+2k)e^{-x}\\cos x-2(2m-2k)e^{-x}\\sin x-\\\\\n-4me^{-x}\\cos x+4ke^{-x}\\sin x=e^{-x}\\sin x\\\\\n\\cos x: -4k-4m-4k-4m=0\\\\\n\\sin x:-4m-4m+4k+4k=1\\\\\nm=-\\frac{1}{16}\\\\\nk=\\frac{1}{16}\\\\\ny_2=\\frac{1}{16}e^{-x}\\cos x-\\frac{1}{16}e^{-x}\\sin x"
than
"y=C_1+C_2x+C_3e^x\\cos x+C_4e^x\\sin x+\\\\\n+(\\frac{2}{5}x+\\frac{43}{25})e^{-x}+\\frac{1}{16}e^{-x}\\cos x-\\frac{1}{16}e^{-x}\\sin x"
Comments
Dear Anurag Dhayal, please use the panel for submitting new questions.
y"-y'=e^x+e^2x+x find the general solution
Leave a comment